Disability and Health Outcomes – From a Cohort of People on Long Term ART - Myezwa Hellen; Hanass-Hancock Jill; Tunde Ajidahun Adedayo; Carpenter Bradley (Journal of Clinical Research In HIV AIDS And Prevention, 2017)
HIV and AIDS remains a major health problem in South Africa even after two decades since the introduction of antiretroviral therapy. Long term survival with HIV is associated with new health related issues and a risk of functional limitation/disability. The aim of this study was to assess the impact and predictors of functional limitation associated with HIV/AIDS among people living with HIV (PLHIV) in South Africa. This study is a cross-sectional survey using a cohort in an urban area in Gauteng province South Africa. Questionnaires that were interview administered were used to collect information on demographics, disability, mental and physical health state, adherence and livelihood. A total of 1044 participants with an average age of 42±12 years, were included in the study and 51.9% of the participants reported functional limitation (WHODAS ≥ 2). These were reported mainly in the participation (40.2%) and mobility domains (38.7%). In addition, adherence to ARV, physical health symptoms and depression were strongly associated with functional limitations/disability. HIV as a chronic disease is associated with functional limitations that are not addressed and pose a risk of long term disability and negative adherence outcomes. Therefore, wellness for people living with HIV/AIDS (PLHIV) needs to include interventions that can prevent and manage disability.
Keywords: HIV